Сучасні тенденції у вирішенні задач виявлення та розпізнавання об′єктів на зображеннях - Лисенко, Геннадій Леонідович; Тарновський, Микола Геннадійович; Кузьменко, Лілія Вікторівна (Vinnytsia National Technical University, 2017)
In the field of image analysis, the desire to create sufficiently universal and at the same time substantially adequate models and procedures for various applications has led to the emergence of various methods of modern computer vision. The paper considers modern approaches to the analysis and recognition of images that encompass a group of methods for recognizing images without a teacher. In particular, the main features of the methods of searching and recognizing objects on images based on correlation and morphological analysis are analyzed.